2006
DOI: 10.1007/s11071-006-2423-5
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Bifurcation and Chaos of a String-Beam Coupled System with Two Degrees-of-Freedom

Abstract: In this paper, research on nonlinear dynamic behavior of a string-beam coupled system subjected to parametric and external excitations is presented. The governing equations of motion are obtained for the nonlinear transverse vibrations of the string-beam coupled system. The Galerkin's method is employed to simplify the governing equations to a set of ordinary differential equations with two degrees-of-freedom. The case of 1:2 internal resonance between the modes of the beam and string, principal parametric res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…[ [27][28][29] regarding the behavior of vibrations and occurrence of jump phenomena and multi-valued amplitudes. (7) From the force response curve we concluded that, the region of multi-valued amplitude is increased for increasing values of ω 1 , ω 2 , α 14 , α 21 , σ and disappear for increasing μ 1 , μ 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ [27][28][29] regarding the behavior of vibrations and occurrence of jump phenomena and multi-valued amplitudes. (7) From the force response curve we concluded that, the region of multi-valued amplitude is increased for increasing values of ω 1 , ω 2 , α 14 , α 21 , σ and disappear for increasing μ 1 , μ 2 .…”
Section: Discussionmentioning
confidence: 99%
“…[27,28], we can obtain the following nonlinear ordinary differential governing equations (ODE) of motion for the string-beam coupled system under external, parametric and tuned excitation forces with two degrees of freedom…”
Section: Equations Of Motions and Perturbation Analysismentioning
confidence: 99%
See 3 more Smart Citations